2015
DOI: 10.1175/jcli-d-14-00410.1
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Daily Temperature and Precipitation Extremes for the Southeastern United States: 1948–2012

Abstract: Spatial and temporal trends in temperature and precipitation extremes were investigated for the period 1948–2012 across the southeastern United States using 27 previously defined indices. Results show that regionwide warming in extreme minimum temperatures and cooling in extreme maximum temperatures occurred. The disproportionate changes in extreme daytime and nighttime temperatures are narrowing diurnal temperature ranges for most locations. The intensity and magnitude of extreme precipitation events increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
88
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(94 citation statements)
references
References 50 publications
6
88
0
Order By: Relevance
“…Finally, a quality control evaluation and a homogeneity assessment of daily precipitation data were performed using the software packages RclimDex and RHtests V4 (http://etccdi.pacificclimate.org/software.shtml). These two programs have been widely used in the quality control, homogenization, and extreme index classification of precipitation data [12,[34][35][36][37][38]. The processes of quality control evaluation and homogeneity assessment include (1) identifying errors in the precipitation data, such as precipitation values below 0 mm; (2) searching for outliers, where we choose 3 standard deviations as the threshold for a fineresolution quality control of the data; (3) using plots of generalized data in RclimDex to visually inspect the data and further identify outliers and a variety of other problems that may cause errors or bias in analysing changes in the seasonal cycles or variance of the data; and (4) using RHtestsV3 to detect artificial shifts that could exist in a time series.…”
Section: Study Region and Data Sourcesmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, a quality control evaluation and a homogeneity assessment of daily precipitation data were performed using the software packages RclimDex and RHtests V4 (http://etccdi.pacificclimate.org/software.shtml). These two programs have been widely used in the quality control, homogenization, and extreme index classification of precipitation data [12,[34][35][36][37][38]. The processes of quality control evaluation and homogeneity assessment include (1) identifying errors in the precipitation data, such as precipitation values below 0 mm; (2) searching for outliers, where we choose 3 standard deviations as the threshold for a fineresolution quality control of the data; (3) using plots of generalized data in RclimDex to visually inspect the data and further identify outliers and a variety of other problems that may cause errors or bias in analysing changes in the seasonal cycles or variance of the data; and (4) using RHtestsV3 to detect artificial shifts that could exist in a time series.…”
Section: Study Region and Data Sourcesmentioning
confidence: 99%
“…Both global [7] and regional [8,9] precipitation characteristics have changed due to the influence of climate change and intensified human activities. A significantly decreasing number of rain days and significantly increasing precipitation intensities have been identified in many places around the world, such as in China [8,10], the United States [11,12], Spain [13], Iraq [14], and Siberia [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the rainfall seasonality analysis in Iran, Talaee et al (2014) noted that rainfall showed a decreasing trend in Iran in the previous years [1,2]. Some researchers [3][4][5][6][7] recognized indirect indications of trend and long-term variability of rainfall. Analysis of rainfall seasonality is important in investigating the influence of climate variability on the regional climate and environmental conditions [5].…”
Section: Introductionmentioning
confidence: 99%
“…The spatial-seasonal forecasts using least squares for precipitation in Iran with additive models are presented in section 3. The forecast model is a least squares method for seasonality estimation and precipitation variations [61]. Since the additive model of seasonality has an acceptable condition, the measuring model has an appropriate quality.…”
Section: Forecast Model For Seasonality and Trend Of Precipitationmentioning
confidence: 99%